Loneliness and Bedtime Procrastination: Exploring a Model of Interconnectedness Among Young Adults in Germany - Trost Sarah; Hast Michael (Journal of Sleep And Sleep Disorder Research, 2024)
Background/Aim This study aimed to examine the relationship between loneliness and bedtime procrastination in young adults in Germany, offering critical insights into the development and maintenance of both conditions. Specifically, it sought to test a new model that connects these two psychological constructs. Materials and Methods A quantitative online survey was conducted with 500 young adults (Mage = 23.3, 83.6% female). Loneliness was assessed using the UCLA Loneliness Scale, while bedtime procrastination was measured using the Bedtime Procrastination Scale. Results The results show a significant positive correlation between loneliness and bedtime procrastination in young adults. Sleep quality was also found to significantly correlate positively with loneliness as well as with bedtime procrastination. Conclusion The findings provide a crucial framework for understanding the relationship between the two psychological constructs of loneliness and bedtime procrastination. Implications for possible future interventions are discussed.
Keywords: loneliness